Beyond Nadsat: The Many Invented Languages of Anthony Burgess. - CLARKE, JIM (Anachronist, 2022)
Anthony Burgess is best-known for his 1962 novella, A Clockwork Orange, which is famously written in Nadsat, the invented language of the protagonist Alex and his gang of droogs. Burgess's invention of Nadsat has gone on to inspire the proliferation of invented languages in fiction, especially in Science Fiction. Just as Burgess's other fictions are less well-known, however, so too are his other forays into invented literary languages. Burgess spent almost the entirety of his career exploring the parameters of invented language in his fiction, and this article aims to describe and taxonomise these many linguistic inventions.